Is pelvic organ prolapse associated with altered microcirculation of the vaginal wall?. Issue 7 (14th July 2015) - Weber, M.A.; Milstein, D.M.J.; Ince, C.; Roovers, J.P.W.R.
Abstract : Aims: Vascularisation of the vagina is necessary for optimal function and support of the surrounding organs. We evaluated whether vaginal microcirculation, as representative of vascularisation, differs between women with and without pelvic organ prolapse (POP). Methods: In 17 women with POP‐Q stage ≥2 and 10 women without POP measurements were performed using sidestream dark‐field imaging (groups were not matched). POP and non‐POP sites were compared in women with a single compartment prolapse (n = 7). Morphology of the microvessels was scored using the microcirculatory architecture and capillary tortuosity scores at four regions of the vaginal wall. Capillary density measurements were performed and microvascular flow was assessed according to the microvascular flow index (MFI) score. Results: Architecture and tortuosity scores were similar for each anatomical region between women with and without POP and between the POP and non‐POP site. A statistically significant difference in capillary density in the left vaginal wall between women with and without POP was observed (25.8 vs. 34.0, P = 0.049). No significant differences in capillary density were observed between the POP and non‐POP site. Average MFI scores revealed a continuous flow for all four regions in patients with and without POP. Conclusions: Vaginal microcirculatory architecture, capillary density, and microvascular flow are similar in women with and without POP. Our method to assess the microcirculation of the vaginal wall is consistent in women with POP, which generates an opportunity to assess vaginal microcirculation in the (surgical) treatments of POP. Neurourol. Urodynam. 35:764–770, 2016 . © 2015 Wiley Periodicals, Inc.